Fabrication of adsorbent using nano-sized lignocellulosic biochar coated on luffa aegyptiaca sponge to remove heavy metal chromium VI - Yulia, Elfi; Purwasasmita, Bambang Sunendar; Nugraha; Ekawati, Estiyanti; Nugraha, Ashari Budi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Eliminating heavy metal Cr (VI) in liquids is challenging. Developing adsorbents using sustainable, cheap, and biodegradable materials is still a concern. Therefore, this study aims to synthesize a heavy metal adsorbent by transforming forest residue into nano-sized lignocellulose biochar. This nano-sized lignocellulosic biochar, with the assistance of chitosan and alginate, was coated onto the Luffa aegyptiaca sponge surface to complete the structure of the proposed heavy metal adsorbent. This adsorbent is easy to apply in adsorbing heavy metals, is durable, and can be reused. The adsorbent products were characterized to observe the functional groups by Fourier Transform Infrared (FTIR) and surface morphology by Scanning Electron Microscopy (SEM). The adsorbents were also experimented with contact times of 120 and 1200 minutes in the adsorption process. The decrease in heavy metal concentration was analyzed by Atomic Absorption Spectroscopy (AAS). Scanning Electron Microscopy with Energy Dispersive X-ray spectroscopy (SEM-EDX) observed the adsorbent surface that has absorbed heavy metal ions. FTIR characterization of surface functional groups showed the presence of hydrogen, aliphatic C-H group, C=C aromatic ring, carboxyl groups, and carbonate ion, capable of binding heavy metal Cr (VI). The morphology of the adsorbent coated on luffa showed that the adsorbent was well attached. The results of the adsorption process showed a decrease in Cr (VI) concentration, with adsorption efficiency reaching 94% for 1200 min and adsorption capacity of 0.36 mg/g. SEM-EDX results validated the attachment of Cr (VI) heavy metal ions to the adsorbent surface.